Testing and validating a conceptual framework for e-collaboration in an undergraduate course - Yussiff, A.-S. (Institute of Electrical and Electronics Engineers Inc., 2016)
Electronic collaboration can provide the environments for educators and learners to connect electronically via the Internet to study together, communicate discuss, and to exchange information and resources from anywhere, anytime and in any place. However, despite the progress registered in the use of e-collaboration system as educational tools through the incorporation of constructivism learning theories and its related didactics in higher educational institution, the approach has not yet been successfully transferred to the classroom. More importantly, there are still misconceptions among researchers regarding students achieving authentic learning from online interaction and collaboration. In an attempt to close this gap, a framework was developed to assist in the design, development and implementation of e-collaboration in a higher education institution. The framework addresses the development process of e-collaboration content, approaches for e-collaboration, pedagogical didactics, learning theories, and roles of users in e-collaboration. In an attempt to validate the framework, an e-collaboration system named 'Teach, Learn, and Research E-collaboration System' (TELERECS), was developed and experimentally implemented in a classroom context. An experimental research design based on control and experimental groups, pre/post-test and usability survey were used to validate the framework. The results revealed that there is significant difference between the post-test mean scores of the experimental and control groups. In addition, there is moderate, positive monotonic correlation between easy to use and post-test-scores; and between useful for team work and post-test-score for the experimental group. These imply that the framework offers a promising basis for meaningful learning. Future work includes a further exploration and validation of the framework and comparing results. Â© 2015 IEEE.